Wake Forest basketball game - (:unkn) unknown (Z. Smith Reynolds Library, 1960)
Photo appeared in Wake Forest Magazine.
Wake Forest player reaching for ball during game.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth